Comparison of chassis frame design of Go-Kart vehicle powered by internal combustion engine and electric motor. (2021) - Chandramohan, Naveen Kumar; Shanmugam, Mohanraj; Sathiyamurthy, S.; Tamil Prabakaran, S.; Saravanakumar, S.; Shaisundaram, V.S.
Abstract: Go-Kart design and development helps in implying the theoretical knowledge into the practical aspect. It also helps to learn about various parameters that can be altered and implied to try to improve the performance of the kart. Go-kart is of various types namely internal combustion engine (IC) powered, Electric driven, solar powered and Hybrid. This project is aimed to convert an IC engine Go-kart into an Electric driven kart, the Frame of the IC engine kart requires a single mount as it needs only Engine and it is developed using SOLIDWORKS, whereas in Electric driven it is a combination of Battery, Motor and Controller and hence it requires a large number of mounts and cross members to support the components, the conversion of IC powered engine frame into an Electric driven needs some alteration to support the components and a new frame was developed using SOLIDWORKS. Both frames are analysed using ANSYS for different types of impacts namely front, side and rear in accordance with the load distribution that acts in the frame and the deformation results are compared.